PENGARUH EDUKASI LAKTASI TERHADAP DUKUNGAN KELUARGA DALAM PEMBERIAN ASI DI KABUPATEN PEKALONGAN - Siti Rofiqoh (Jurnal Ilmu Keperawatan dan Kebidanan, 2020)
Abstract Family support is needed to help mothers breastfeed their babies, but family knowledge about lactation management is lacking. Sufficient knowledge is needed in the family so that they can help mothers in breastfeeding. This study aims to analyze the effectiveness of lactation management education packages for family support for mothers in breastfeeding. Quasi-experimental research method with a post test control group design. The place of research was in the Buaran and Puskesmas Wonokerto 2 work areas with the 3rd trimester primigravida respondents. Mothers whose milk did not come out and the baby died was excluded. The sampling technique uses multistage sampling. Interventions in the form of lactation management education for mothers and families every month 3 times during pregnancy in the third trimester. Statistical test using independent t test. The results showed an average family support in the control group 61.43 (55-78) and in the intervention group 68.10 (46-76) with a p value of 0.001 in 95% CI. The conclusion is the effect of giving lactation management education to family support for mothers in giving breast milk. Advice for health workers is expected to further improve lactation management education activities in families of pregnant women. Keywords: education, family support, , lactation management.